Musical Creation “Poleng” | Musik Kreasi Poleng - ikadekagus adityaputra; I Gede Yudarta; Hendra Santosa (GHURNITA: Jurnal Seni Karawitan, 2022)
The symbols of Hindus in Bali are generally in the form of objects with various shapes or the use of cloth with certain colors. This shows that color has an important meaning for Hindus in carrying out worship. One color combination that is often used is a combination of black and white that is configured in such a way on a piece of cloth. Poleng cloth is the name of the cloth that is patterned like a chessboard that we often encounter. Poleng cloth has its own meaning and philosophy in each type of cloth. While the word Poleng has the term black and white which is a symbol of the balance of nature. The symbol is named Rwabhineda according to Hinduism. From this phenomenon this work was created. Poleng is a composition of new creations packed with traditional nuances. This work is an interpretation of Rwabihineda's poleng visual mechanism, which focuses on the work of two contradictory traits. Poleng's work uses the Semarpegulingan gamelan as a medium of expression. The process of creating this work is carried out in four stages, namely initial stimulation combined with the concept of Alma M. Hawkins in the book Creating Trough Dance which consists of exploration, improvisation, formation. This work is manifested in the creation of percussion which is still based on the realm of tradition, the forms contained in this work lie in the formulation of the development of musical patterns as the basis for the formation of the work.